End-of-life decisions in the newborn period: attitudes and practices of doctors and nurses - (:unkn) unknown (TURKISH J PEDIATRICS, 2009)
The aim of our study was to assess the attitudes and practices of doctors and nurses about end-of-life decisions and compare our results with those observed in different European countries. The data was collected from nurses and doctors, using a standardized questionnaire adapted from the EURONIC study. A total of 250 structured questionnaires were delivered, and 135 (77%) of them were accepted for analysis. The end-of-life decision was taken in 39.4% of the hospitals and personal involvement was 40%. Although an ethical committee was present in the hospitals of 61.5% of responders, a written policy was present in only 3.1% of the units. The mean attitude score was 6.5. Seventy-five percent of the contributors agreed that everything possible should be done to ensure a neonate's survival regardless of the prognosis and 65.2% of responders believed that costs of health care should not affect nontreatment decisions. Most of the responders (65.2%) agreed that severe mental disability as an outcome was equal to or worse than death. In patients in whom medical intervention would be futile or would dot offer sufficient benefit to justify the burdens imposed, hospitals should set up a functional ethical committee in order to decide in matters of withholding or withdrawing intervention.
Keywords: end-of-life decision; newborn; euthenasia; SELF-REPORTED PRACTICES; EUROPEAN COUNTRIES; INTENSIVE-CARE